Antitumor effect of pyrrolo-1, 5-benzoxazepine-15 and its synergistic effect with Oxaliplatin and 5-FU in colorectal cancer cells. Issue 8 (2nd August 2016) - Fiore, Donatella; Proto, Maria Chiara; Pisanti, Simona; Picardi, Paola; Pagano Zottola, Antonio Christian; Butini, Stefania; Gemma, Sandra; Casagni, Alice; Laezza, Chiara; Vitale, Mario; Ligresti, Alessia; Di Marzo, Vincenzo; et al.
ABSTRACT: Some compounds of a series of novel pyrrolo-1, 5-benzoxa(thia)zepine, a well-known group of tubulin targeting agents, display anti-tumor effects mainly inducing cell cycle arrest and apoptosis in several human cancer models. A member of this family, pyrrolo-1, 5-benzoxazepine-15 (PBOX-15), has previously shown potent pro-apoptotic activity in a variety of human tumor cell types, with minimal toxicity toward normal blood and bone marrow cells. In this study, we evaluated the PBOX-15-mediated effects in human colorectal cancer cell (CRC) lines, DLD-1 and HT-29. The compound, used at concentrations equal to or greater than 1 μM, inhibited the proliferation of human CRC cells, inducing a significant cell cycle arrest in the G2/M phase. In DLD-1 cells, treatments prolonged over 48 h triggered a strong activation of the intrinsic apoptotic pathway as indicated by activation of caspase-9, caspase-3 and PARP cleavage. Moreover, nanomolar concentrations of PBOX-15, significantly improved the oxaliplatin and 5-fluouracil-induced anti-proliferative effects in DLD1 cell line. The observed synergistic interaction of both PBOX-15/Oxaliplatin and PBOX-15/5FU may involve activation of p38 MAPK and JNK pathway, which in turn significantly increased caspase-3 cleavage in DLD-1 cells, treated with PBOX-5/Oxaliplatin but not with PBOX-15/5FU. Moreover, PBOX-15/5FU-treated cells showed an increase in expression of the pro-apoptotic protein Bax. Taken together, these results show that PBOX-15 could represent a promising compound for the treatment of human CRC and a strong candidate for novel therapeutic options.